Utilizing Telemedicine and Modified Fibrosis Staging Protocols to Maintain Treatment Initiation and Adherence Among Hepatitis C Patients During the COVID-19 Pandemic - Matthew O'Brien; Rachel Daws; Pooja Amin; Kristen Lee (SAGE Publishing, 2022)
The COVID-19 pandemic exacerbated the decline in Hepatitis C Virus (HCV) screening and treatment globally in part due to lockdowns and restrictions at healthcare centers. The goal of this retrospective cohort study was to assess the effectiveness of an updated workflow implemented at Boston Medical Center (BMC) HCV clinics. Revised workflow incorporated appointments via telemedicine, transitioning to blood test-based fibrosis scoring, and delivering medication by mail to mitigate the lack of in-person services. We compared 2 cohorts of patients who attended at least the initial intake appointment at BMCHCV clinics: 170 before the pandemic and 133 after the pandemic. Outcome variables included treatment starts, fibrosis lab tests completed, appointment attendance, and SVR achievement. Proportions for outcome variables were compared between groups by use of χ 2 and 2-sample t -tests where appropriate. Our results showed a 14.43% decrease in completing fibrosis scoring tests ( P -value: <.001) and a 15.21% decrease in medication initiation ( P -value: <.001) among the patients who initiated care during the pandemic (modified workflow group). Furthermore, we found a 18.56% decrease in sustained virologic response (SVR) among the modified workflow group when compared to the controls. Overall, these results align with current trends of patients' decreasing engagement in HCV care but show higher retention than other published data. Furthermore, these figures support how appointments via telemedicine, transitioning to blood test-based fibrosis scoring, and medication delivery by mail can serve as tools to increase access to HCV care and successful HCV treatment completion even after COVID restrictions are lifted.